IMPLEMENTASI SISTEM AERATOR SUBMERGED TURBINE POSISI VERTIKAL SUMBER ENERGI PLTS - Musrady Mulyadi; Abdul Rahman; Sri Suwasti (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Shrimp farming is an agricultural sector that can boost income and improve the national economy. However, aeration is crucial for shrimp growth and productivity due to the lack of water flow. Aeration involves adding air into the water to maintain sufficient oxygen levels in shrimp ponds. The process starts with generating electrical energy for the submerged turbine aerator electric motor, which is used to drive a waterwheel in the pond. The rotating turbine then produces aeration. Tests have been conducted using solar energy to power the submerged turbine aerator at different rotations. At 1000 rpm pinwheel rotation, the average power was 69.11 Watts with a solar panel efficiency of 4%. At 1500 rpm, the average power was 83.19 Watts with a solar panel efficiency of 7.09%. Finally, at 2000 rpm rotation, the average power was 119.2 Watts with a solar panel efficiency of 4.12%. These findings indicate the potential of using solar energy for aeration in shrimp farming.